RETRACTED: The Impact of Green Investment, Technological Innovation, and Globalization on CO2 Emissions: Evidence From MINT Countries - Li, Shijie; Yu, Yang; Jahanger, Atif; Usman, Muhammad; Ning, Yifan (Frontiers in Environmental Science, 2022)
The Mexico, Indonesia, Nigeria, and Turkey (MINT) countries have practiced significant levels of economic growth over the years. However, these countries have not handled to protect their environmental quality in tandem. Thus, the environmental indicators aggravation transversely these countries radiate an uncertainty shadow on the achievements of the economic growth sustainability in these countries. In this regard, green investment and technology innovations are commonly considered as an effective aspect to minimize CO2 emissions as these increase energy efficacy and cleaner production. Thus, this study investigates the effect of green investment, economic growth, technological innovation, non-renewable energy use, and globalization on the carbon dioxide (CO2) emissions in MINT countries from 2000 to 2020. After checking the stationary process, this study applied fully modified ordinary least square (FMOLS) and dynamic ordinary least square (DOLS) methods to estimate the long-run elasticity of the mentioned regressors on CO2 emissions. The outcomes show that non-renewable energy and technological innovations significantly increase environmental degradation. In contrast, the globalization process and green investment significantly reduce it in the long run. Moreover, the interaction effect of green investment and globalization significantly overcome the pressure on the environment. Similarly, the moderation effect of technological innovation and globalization significantly reduce the emission level in the region. Moreover, the U-shaped environmental Kuznets curve (EKC) hypothesis was observed between economic growth and carbon emission across the MINT countries. Furthermore, the findings of the Dumitrescu and Hurlin's panel causal test disclose a bidirectional causality exist between green investment, globalization, technological innovations, non-renewable energy, and CO2 emissions. This study also recommends some valuable policy suggestions to governments and policymakers in general/specific regarding the developing world for endorsing their environmental sustainability.